Metode Berbasis Teks dalam Pembelajaran Bahasa Indonesia terhadap Kemampuan Kognitif Siswa Sekolah Dasar - Cindy Widiyanti; Ishmatun Naila; Lilik Binti Mirnawati (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine and review the impact of language learning through text-based methods on the cognitive abilities of elementary school students. The research approach used is a qualitative study with the main instrument being the researcher, and supporting instruments including observation, interviews, and documentation of student learning outcomes at the elementary school level. Research data was obtained from various library sources, such as books, scientific articles, national and international journals, and other relevant scientific works related to text-based learning and student cognitive development. The results of the study indicate that the implementation of Indonesian language learning with text-based methods has a diverse impact on students. Differences in learning outcomes are not only influenced by the strategies and learning processes implemented by teachers, but are also closely related to students' cognitive abilities in understanding, interpreting, and processing information from Indonesian texts. Thus, text-based methods need to be adapted to the characteristics and levels of students' cognitive abilities so that learning objectives can be optimally achieved.